Translating Global into Local/Local to Global Learning into Teaching Practices (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
During an eight month period in 2019 the researchers conducted case study classroom-based observations and pursued conversations with ten study abroad participants from four Fulbright-Hays study abroad programs (India, South Korea, Israel, SeneGambia). Observing, documenting and reflecting on the translation of global to local and local to global academic, cultural and pedagogical insights in the work of the preservice and in-service teachers is the focus of the grounded theory qualitative research study. Global experiential learning for college students is repeatedly described as transformative, while research studies have indicated the difficulty in identifying specific outcomes of short term study abroad experiences. By working with preservice and in-service teachers, this qualitative case study researches new conceptual perspectives and quotidian meaning-making practices in actual classrooms. The coded grounded theory case study research details turn-key classroom activities and reflections on four select themes of multilingualism, gender/racial diversity, holocaust/genocide education/social and emotional learning, and the universal language of technology and the arts framed by conceptual understandings of cosmopolitanism and critical consciousness.